THU0572-HPR Osteomalacia: Developing an Interactive Education Tool for South Asian Populations. (10th June 2014) - Robinson, S.; Adebajo, A.; Heliwell, P.; Rahman, A.; Raza, K.; Samanta, A.; Johnson, M.; Bishop, P.; Kumar, K.; Walker, D.
Abstract : Background: Osteomalacia is a significant population health risk that preferentially affects darker skinned people where English may not be the first language. Objectives: We were interested to develop an e-based interactive, multi language tool, based on the Mind-Map and giving information in an accessible layered fashion suitable for people with poor English language skills. Methods: The Mind-Map wasused as the "home" page. Hyperlinks gave the user options to link to more detailed information. It was possible to take any route through the information and to return from any screen to the original Mind-Map screen. The tool was designed to give the user information in layers. The first layers of the tool are the basic knowledge the user requires to make informed decisions and choices. Further layers lead the user to more in depth information and links to the internet. Only the first layer of the tool was translated into Urdu. The translation was reviewed by a panel of six educated Urdu speakers in the UK to ensure that the translation was correct. A focus group of 10 Urdu speakers from Stourbridge was used to test the tool. A presentation using the tool was performed and their reactions to it recorded. The participants were given the DVD to take away with them. Two months later the group was reconvened and the discussion recorded and transcribed. Results: All participants felt that they had learned a lot about Osteomalacia. There was a feeling that this was a very important issue and they were surprised how little they knew about it. The content was judged to be of appropriate detail. It was felt that only the first layer would be used in a presentation but some users may be interested in having more information. It was also suggested that presenting it in English to encourage people to speak enough English to interact with healthcare professionals would be helpful. There were suggestions on how this should be used with presentations in communities but also in schools. They felt that this was a community tool rather than just hospital based. One participant had already given presentations to their community and reported very good informal feedback. Conclusions: We have produced a bi-lingual interactive tool to educate people about Osteomalacia and its treatment. Initial reactions show it to be suitable for the intended audience. We now intend to study this for knowledge transfer and change of behaviour. Acknowledgements: We would like to acknowledge the contribution of the focus group from Stourbridge Birmingham. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4424